Natural Polymers for Wound Dressing Applications - ALARÇİN, EMİNE (Elsevier, 2022)
Wound care is a hot topic in recent years. Recent wound treatment regimens use dressings fabricated from natural materials due to their significant advantages compared to traditional or synthetic dressings. Because of their importance, in this chapter, wound dressings are discussed with an emphasis on the use of natural polymers and their function in the healing process. After a brief introduction to wounds and classification of wound dressings, the chapter focuses on (i) the impact of natural materials on wound dressing design such as mechanical properties, texture, wettability, composition, and porosity; (ii) commonly used natural polymers and their combinations with synthetic polymers and other bioactive components; (iii) state-of-the-art fabrication methods of dressings; and finally, (iv) other nature-derived materials as wound dressings such as decellularized skin extracellular matrix and tissue-engineered skin substitutes.